65 successful Harvard Business School application essays : with analysis by the staff of the Harbus, The Harvard Business School Sewspaper - Sullivan, Lauren (New York : St. Martin's Griffin, 2009)
A collection of 65 business school application essays and their detailed analysis of them so that applicants: avoid common pitfalls; play to their strengths; and, get their message across.
Keywords: Harvard Business School; Business schools -- Admission. -- United States; Exposition (Rhetoric).